Investigation of FGF21 mRNA levels and relative mitochondrial DNA copy number levels and their relation in nonalcoholic fatty liver disease: a case-control study - Houshmand, Massoud; Zeinali, Vahide; Hosseini, Amirhossein; Seifi, Atena; Danaei, Bardia; Kamfar, Sharareh (Frontiers in Molecular Biosciences, 2023)
Background: Although the exact mechanisms of non-alcoholic fatty liver disease (NAFLD) are not fully understood, numerous pieces of evidence show the variations in mitochondrial DNA (mtDNA) and hepatic Fibroblast growth factor 21 (FGF21) expression may be related to NAFLD susceptibility. Objectives: The main objective of this study was to determine relative levels of mtDNA copy number and hepatic FGF21 expression in a cohort of Iranian NAFLD patients and evaluate the possible relationship. Methods: This study included 27 NAFLD patients (10 with nonalcoholic fatty liver (NAFL) and 17 with non-alcoholic steatohepatitis (NASH)) and ten healthy subjects. Total RNA and genomic DNA were extracted from liver tissue samples, and then mtDNA copy number and FGF21 expression levels were assessed by quantitative real-time PCR. Results: The relative level of hepatic mtDNA copy number was 3.9-fold higher in patients than in controls (P<0.0001). NAFLD patients showed a 2.9-fold increase in hepatic FGF21 expression compared to controls (P<0.013). Results showed that hepatic FGF21 expression was positively correlated with BMI, serum ALT, and AST levels (P<0.05). The level of mitochondrial copy number and hepatic FGF21 expression was not significantly associated with stages of change in hepatic steatosis. Finally, there was a significant correlation between FGF21 expression and mitochondrial copy number in NAFLD patients (P=0.027). Conclusions: These findings suggest that the increase in hepatic FGF21 expression and mtDNA copy number in the first stage of NAFLD may be a compensatory protective mechanism in response to oxidative stress damage in patients.